Pengaruh Konten Instagram Wisata Budaya terhadap Minat Berkunjung Wisatawan Generasi Z di Kota Bandung - Hanifah, Sofina Denisya; Ghani, Yosef Abdul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the influence of Instagram content featuring cultural tourism destinations on the interest in visiting Generation Z tourists in Bandung City. The method used is quantitative with a survey approach with a sample of 200 Generation Z respondents (born 1997–2012) who actively use Instagram in Bandung. The research instrument was a Likert scale questionnaire 1–4, analyzed with descriptive statistics and simple linear regression. The results show that the perception of Instagram content is generally positive: 55% of respondents agree that Studio Rosid videos are visually appealing and 32.5% strongly agree that cultural information is easy to understand. Regression tests reveal that the effectiveness of Instagram content has a significant positive effect on interest in visiting (β=0.221; t=3.067; p=0.002), although it can explain 4.5% of the variation in interest in visiting (R²=0.045). The most dominant indicator influencing interest in visiting is the visual aspect (images/videos), with 47% of respondents strongly agreeing that Instagram videos are very interesting. This finding confirms the importance of the quality of visual content in encouraging Generation Z's interest in cultural tourism.